Cover page of steel structure as-built drawing of BRAC University New Campus Project - BUCG-ABC Joint Venture (BUCG-ABC JV) (BRAC University, 2024)
This record contains structural as-built drawings of the steel structure of the Brac University New Campus Project. It consists of both PDF and DWG versions of the drawings.